Cortical Thickness in Mild Traumatic Brain Injury - Govindarajan, Koushik A.; Narayana, Ponnada A.; Hasan, Khader M.; Wilde, Elisabeth A.; Levin, Harvey S.; Hunter, Jill V.; Miller, Emmy R.; Patel, Vipul Kumar S.; Robertson, Claudia S.; McCarthy, James J. (Journal of neurotrauma, 2016)
Magnetic resonance imaging data were acquired at ∼24 h and ∼3 months post-injury on mild traumatic brain injury (mTBI; n = 75) and orthopedic injury (n = 60) cohorts. The mTBI subjects were randomly assigned to a treatment group with atorvastatin or a non-treatment mTBI group. The treatment group was further divided into drug and placebo subgroups. FreeSurfer software package was used to compute cortical thickness based on the three dimensional T1-weighted images at both time-points. Cross-sectional analysis was carried out to compare cortical thickness between the mTBI and control groups. Longitudinal unbiased templates were generated for all subjects and cortical thickness measurements were compared between baseline and follow-up scans in the mTBI group. At baseline, significant reduction in cortical thickness was observed in the left middle temporal and the right superior parietal regions in the mTBI group, relative to the control group (p = 0.01). At follow-up, significant cortical thinning was again observed in the left middle temporal cortex in the mTBI group. Further analysis revealed significant cortical thinning only in the non-treatment group relative to the control group. In the follow-up, small regions with significant but subtle cortical thinning and thickening were seen in the frontal, temporal, and parietal lobes in the left hemisphere in the non-treatment group only. Our results indicate that cortical thickness could serve as a useful measure in identifying subtle changes in mTBI patients.